2015
DOI: 10.1002/uog.13449
|View full text |Cite
|
Sign up to set email alerts
|

Time‐interval analysis of ductus venosus flow velocity waveforms in twin‐to‐twin transfusion syndrome treated with laser surgery

Abstract: Objectives To investigate time-interval variables of ductus venosus (DV) flow velocity waveforms (FVWs) in twin-to-twin transfusion syndrome (TTTS), comparingthe results with reference ranges from normal singleton fetuses. The impact of laser surgery and the effect of prognostic factors were also evaluated. S and D, respectively). For each variable, Z-scores were calculated with respect to previously reported normal reference ranges. Methods In 107 TTTS cases, DV-FVWs of both recipients and donors were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…The awareness of ductus venosus time intervals can also be of benefit in terms of monitoring the response to treatment. Tachibana et al reported significant divergences of time interval measurements after fetoscopic laser coagulation of anastomotic vessels; a decreased systolic deceleration time with a simultaneously increased diastolic acceleration time in the recipients may reflect an improvement in cardiac function …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The awareness of ductus venosus time intervals can also be of benefit in terms of monitoring the response to treatment. Tachibana et al reported significant divergences of time interval measurements after fetoscopic laser coagulation of anastomotic vessels; a decreased systolic deceleration time with a simultaneously increased diastolic acceleration time in the recipients may reflect an improvement in cardiac function …”
Section: Discussionsupporting
confidence: 90%
“…Our study found alterations of the ductus venosus time interval variables even in the early stages of twin‐twin transfusion syndrome. The shortening acceleration phase of ventricular contraction in the donor twins was in accordance with a previous report . Another study suggested that the reduction of the systolic time was caused by decreased ejection forces and cardiac output from hypovolemia .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Both preload and afterload are altered by SFLP, demonstrated by a significant decrease in DV pulsatility index and normalization of time intervals with lengthening of filling times, reflecting improved diastolic heart function in the recipient . This is also shown in a significant improvement of left‐ and right‐ventricular Tei index and an increase in the shortening fraction after SFLP .…”
Section: Antenatal Therapy and Its Implication On The Cardiovascular mentioning
confidence: 96%
“…Previous studies have shown shortened filling times in the recipients' DV in twin–twin transfusion syndrome (TTTS). Attempts to classify DV velocity patterns have been undertaken in fetuses with altered PIV, including twins complicated by TTTS, but have not shown a specific velocity pattern.…”
Section: Introductionmentioning
confidence: 99%